Effect of smoking and fat content on the dynamic perception of bacon by Brazilian consumers - Saldaña, Erick (2019)
The high heterogeneity of meat and meat products can influence the sensory perception of the consumers, being necessary to measure the real impact of these non-controllable variables on the dynamic sensory properties of the smoked bacon during tasting. The aim of this study was to evaluate the effect of smoking and fat content on the dynamic sensory perception of bacon by Brazilian consumers. For this, four different samples were prepared, varying the fat content (from “low” to “high”) and the type of smoking shown on the product label (natural and artificial). Thirty-five habitual smoked bacon consumers evaluated the dynamic sensory properties of the product using the Temporal Dominance of Sensations (TDS) method. The results were submitted to univariate (bandplot by attribute) and multivariate analyzes (Principal Component Analysis) to study both the dominance rate and its duration, respectively. The main attributes modified during tasting were "salty," "fatty," and "succulent," thus showing that the dynamic sensory perception of smoked bacon was modified by the type of smoking and the fat content of the sample.